Resimen Mahasiswa (Menwa) and its Development at Universitas Negeri Semarang Campus 1976-2000 - Jouhar, Jouhar Hanin Afalia; Utama, Nanda Julian (Journal of Indonesian History, 2024)
This research discusses the track record of a student organization called Menwa at the UNNES campus from 1976 to 2000. Menwa UNNES was established in 1976, with its first headquarters in the Karya Graha building, Kelud campus of IKIP Semarang. This research uses historical methods, beginning with collecting sources known as heuristics. These sources consist of archival documents and interviews, supported by secondary sources as complements. The author then interprets the collected data, determining the interconnected meanings of the obtained facts to form a coherent narrative. The final stage is historiography or writing the findings from the research process. The research results show that the existence of Menwa within the UNNES campus aimed to create state defense cadres and maintain a sense of patriotism among students despite rejection from several groups. Similar issues occurred on other campuses. At its peak, renewing the Menwa SKB to resolve frequent disputes became necessary. Menwa experienced ups and downs due to various internal and external factors. Despite these challenges, Menwa UNNES significantly impacted the campus, achieving accomplishments and serving the community at both national and international levels.